2017
DOI: 10.1016/j.ymthe.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-Modified Gapmer Antisense Oligonucleotide and Serum Albumin Constructs for Pharmacokinetic Modulation

Abstract: Delivery technologies are required for realizing the clinical potential of molecular medicines. This work presents an alternative technology to preformulated delivery systems by harnessing the natural transport properties of serum albumin using endogenous binding of gapmer antisense oligonucleotides (ASOs)/albumin constructs. We show by an electrophoretic mobility assay that fatty acid-modified gapmer and human serum albumin (HSA) can self-assemble into constructs that offer favorable pharmacokinetics. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Gapmers offer the benefit of modifications for stability and reduced toxicity, while still allowing engagement of the RNase H pathway (Fig. 3B) [159].…”
Section: Antisense Oligonucleotides (Asos)mentioning
confidence: 99%
“…Gapmers offer the benefit of modifications for stability and reduced toxicity, while still allowing engagement of the RNase H pathway (Fig. 3B) [159].…”
Section: Antisense Oligonucleotides (Asos)mentioning
confidence: 99%
“…The approach exploits the natural ligand binding and transport properties of albumin as a result of interaction with fatty acid‐modified drug molecules. We showed that palmitoylated gapmers can strongly bind to serum albumin and exhibit a prolonged serum half‐life . An in‐depth investigation into the effect of gapmer designs on gene silencing, however, was not conducted.…”
Section: Introductionmentioning
confidence: 98%
“…A typical gapmer contains a short central block of antisense DNA nucleotides for activating RNase H‐mediated mRNA degradation, flanked at each end by modified nucleotides such as locked nucleic acid (LNA), 2′‐ O ‐methyl or 2′‐ O ‐methoxyethyl nucleotides for increased stability . Gapmer modifications have been focused toward maximizing silencing activity and a prolonged serum half‐life by inclusion of α‐ l ‐LNA 3 and N2′‐palmitoylated 2′‐amino‐LNA nucleotides (Figure ) . A large number of antisense studies have utilized phosphorothioate (PS) gapmers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 2′amino-LNA, a 2′,4′-bridged nucleic acid, can have various substituents of the 2′-amino group [14]; therefore, 2′-amino-LNA would be a useful scaffold to explore oligonucleotides possessing the desired properties. Previous studies have reported oligonucleotides containing 2′-N-substituted 2′amino-LNA derivatives, such as 2′-N-alkyl, 2′-N-acyl, and 2′-N-alkoxycarbonyl derivatives [15][16][17][18][19][20][21][22]. In general, the synthesis was based on a common method using each modified phosphoramidite; however, post-synthetic approaches using click chemistry [20,21,23] and amidation [24] were also applied to the synthesis of the 2′-N-substituted 2′-amino-LNA derivatives in the oligonucleotides (Figure 1).…”
Section: Introductionmentioning
confidence: 99%